Human papillomavirus genotype prevalence in invasive penile cancers from a registry-based United States population - Hernandez, Brenda Y.; Goodman, Marc T.; Unger, Elizabeth; Steinau, Martin; Powers, Amy; Lynch, Charles F.; Cozen, Wendy; Saber, Maria S.; Peters, Edward S.; Wilkinson, Edward J.; Copeland, Glenn; Hopenhayn, Claudia; et al. (Frontiers in Oncology, 2014)
Background: Human papillomavirus (HPV) is estimated to play an etiologic role in 40–50% of penile cancers worldwide. Estimates of HPV prevalence in U.S. penile cancer cases are limited. Methods: HPV DNA was evaluated in tumor tissue from 79 invasive penile cancer patients diagnosed in 1998–2005 within the catchment areas of seven U.S. cancer registries. HPV was genotyped using PCR-based Linear Array and INNO-LiPA assays and compared by demographic, clinical, and pathologic characteristics and survival. Histological classification was also obtained by independent pathology review. Results: HPV DNA was present in 50 of 79 (63%) of invasive penile cancer cases. Sixteen viral genotypes were detected. HPV 16, found in 46% (36/79) of all cases (72% of HPV-positive cases) was the most prevalent genotype followed equally by HPV 18, 33, and 45, each of which comprised 5% of all cases. Multiple genotypes were detected in 18% of viral positive cases. HPV prevalence did not significantly vary by age, race/ethnicity, population size of geographic region, cancer stage, histology, grade, penile subsite, or prior cancer history. Penile cases diagnosed in more recent years were more likely to be HPV-positive. Overall survival did not significantly vary by HPV status. Conclusion: The relatively high prevalence of HPV in our study population provides limited evidence of a more prominent and, possibly, increasing role of infection in penile carcinogenesis in the U.S. compared to other parts of the world.